Affixation on a News Article Titled Akhir Desember Proyek Pengaman Pantai di Teluk Jakarta Kelar Dibangun - Laurensia Elya Puspita; Fifin Dwi Saputri; Karmelia Ohoilulin (Musamus Journal of Language and Literature, 2024)
The study examines the analysis of affixation in a news article “Akhir Desember Pproyek Pengaman Pantai di Teluk Jakarta Kelar Dibangun” Edition (2024). The purpose of this study was to describe the affixation analysis contained in a news article entitled Akhir Desember Pproyek Pengaman Pantai di Teluk Jakarta Kelar Dibangun. The theory used by morphology about affixation. The type of research used is qualitative. The data collection technique uses reading and recording techniques. The data analysis technique uses morphological studies. The data in this study is a sentence that contains affixation in a news article article entitled Akhir Desember Pproyek Pengaman Pantai di Teluk Jakarta Kelar Dibangun Edition (2024). The data source is a news article entitled ' Akhir Desember Pproyek Pengaman Pantai di Teluk Jakarta Kelar Dibangun Edition (2024). The results of this study show that the types of affixation are divided into 3, namely prefix which means a suffix located in front or beginning, suffix means a suffix which is usually used as a change of meaning or class of words from a base word to a new word. Confix (combination of prefix and suffix). In this study, there are 9 Prefixes, 3 Suflics and 19 Confixes.